É tempo de travessia: os múltiplos caminhos de jovens universitários para a vida adulta - Ginzel, Flávia (Universidade Federal de São Carlos, 2017)
The main objective of this research is to understand the transition modes for the adult life of University students. From comprehensive interviews guided by a semi-directive script, we sought to understand a set of experiences and challenges - especially in the University, in the world of work and in family life - that could be revealing of the processes of transition to adult life lived by ten young people - five girls and five boys - who study at the Federal University of São Carlos - Sorocaba campus. Held between the years of 2015 and 2016, the study focused on students from different courses and social insertions who had already attended at least half of their degree. The analysis of their narratives evidenced a multiplicity of trajectories, which are characterized by non-linear biographical pathways. The study revealed the importance of the new policies of access and permanence in the University, which have promoted a growing heterogeneity of subjects in a space historically restricted to the elites. In addition, it was possible to observe that while the trajectories are increasingly heterogeneous and unique, structural issues - especially linked to social origin and gender - appear as common challenges to be faced by girls and boys in their processes to conquer autonomy and Independence.
It's a time of crossing: the multiple paths of university students towards adult life
Keywords: Ensino superior; Estudantes universitários; Juventude - Educação (superior); Sociologia da Juventude; Transição para a vida adulta; Sociology of Youth; Transition to adult life; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO